On mask layout partitioning for electron projection lithography - Tian, Ruiqi; Yu, Ronggang; Tang, Xiaoping; Wong, D. F. (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2002)
Electron projection lithography (EPL) is a leading candidate for next generation lithography (NGL) in VLSI production. The membrane mask used in EPL is divided into sub-fields by struts for structural support. A layout must be partitioned into these sub-fields on mask and then stitched back together by the EPL tool on wafer. To minimize possible stitching errors, partitioning of a mask layout should minimize cuts of layout features in the overlapping area between two adjacent sub-fields. This paper presents the first formulation of the mask layout partitioning problem for EPL as a graph problem. The graph formulation is optimally solved with a shortest path approach. Two other techniques are also presented to speed up computation. Experimental runs on data from a real industry design show excellent results.